Efficacy of pest management practices against pest complex of okra (Abelmoschus esculentus) in Andaman - BIRAH, AJANTA; SRIVASTAVA, R C; KUMAR, KRISHNA; SINGH, P K; BHAGAT, SOMESHWAR (The Indian Journal of Agricultural Sciences, 2012)
Field trials were conducted during 2008–09 and 2009–10 with okra (Abelmoschus esculentus—variety Arka Anamika) to evaluate the pest management modules against sucking pest complex, jassid (Amrasca devastans Dist.) and whitefly (Bemisia tabaci Genn) and okra shoot and fruit borer, Earias vittella (Fab.). The fruit damage by shoot and fruit borer was significantly lower in all the modules as compared to control at each picking as well as in pooled analysis. Integrated module included seed treatment with imidacloprid @ 5 g/kg seed a day before sowing + sowing of maize at the borders as barrier crop + weekly clipping of infested shoots and fruits + erection of pheromone trap @ 100 traps/ha for mass trapping + foliar spray of neem seed kernel extract @ 30 ml/litre, spinosad 45 SC @ 0.5ml/litre and karanj oil @ 30 ml/litre at 45, 60 and 75 days after sowing, respectively. The pooled data revealed that integrated module and bio-intensive module recorded significantly lower jassid population (3.32 jassids/leaf, 4.27 jassids/leaf) than farmer’s practices (5.31 jassids/leaf) and untreated control (10.12 jassids/leaf). Less incidence of shoot borer (4.23%) and fruit borer (5.64%) and more fruit yield (8.66 tonnes/ha) was recorded in integrated module as compared to untreated control, 13.42%, 16.85% and fruit yield of 5.25 tonnes/ha respectively. The results revealed that different types of management practices have significantly reduced jassid, whitefly population and shoot and fruit borer damage than untreated control in okra. By incorporating these management practices, application of synthetic insecticides can be reduced to a minimum possible level.